Implementasi Isak 35 Pada Organisasi Nirlaba (Studi Kasus Pada KNPI Kabupaten Brebes) - Yusri Anis Faidah; Nurul Mahmudah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
Nonprofit organizations play a strategic role in social and community development and are required to manage and account for financial resources in a transparent and accountable manner. The implementation of Interpretation of Financial Accounting Standards (ISAK) No. 35 concerning the Presentation of Financial Statements of Nonprofit-Oriented Entities is expected to improve the quality and accountability of nonprofit financial reporting. This study aims to analyze the implementation of ISAK 35 and its implications for financial reporting accountability at the Indonesian National Youth Committee (Komite Nasional Pemuda Indonesia/KNPI) of Brebes Regency. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Primary data were obtained from interviews with organizational management, while secondary data were derived from organizational documents and relevant regulations. The findings indicate that the implementation of ISAK 35 at KNPI Brebes Regency remains limited, with only approximately 30 percent of the standard requirements applied. Financial reporting practices are still confined to cash inflow and cash outflow records, without the preparation of comprehensive financial statements as mandated by ISAK 35. This condition results in low levels of financial accountability and transparency, with reporting practices focusing more on activity accountability rather than comprehensive financial accountability.